How sustainable renewable district heating supply and heat saving demand support the transformation of coal energy systems - Dragusha, Bedri; Drilon, Meha; Selimaj, Rexhep; Sahiti, Naser (International Journal of Sustainable Energy Planning and Management, 2025)
Smart district heating systems play a major role in the sustainable energy conversation and utilization processes within energy systems by providing a novel and highly efficient way of supplying buildings with heat. This paper aims to advance the practical understanding and transformation of current use of coal cogeneration units by assessing the benefits of integrating higher efficient energy supply technologies in district heating while simultaneously modelling heat demand reduction in buildings. A bottom-up model was developed for capital city of Kosovo “Prishtina” using the referent year 2018 as a base case as the heating demand and district heating potential maps were generated for this year in previous research. Several scenarios for both district heating supply and building heat demand framed by existing and future policies were investigated. Among other the expansion of district heating system, renewable wind integration via large-scale heat pumps with thermal storage, solar thermal heating production with seasonal heat storage, changes in individual heating solutions and heat demand savings in buildings have been modelled and discussed in this article. The EnergyPLAN model was used to assess the share of primary energy supply savings for individual & district heating, electricity produced via wind turbines, while considering the synergies of sector coupling in an energy system with lowering CO2 emissions. The findings show that developed strategies for decarbonized heating and electricity sector and heat savings in buildings significantly impact the reduction in primary energy supply, renewable electricity production in an energy system with increasing flexibility and CO2 emission reduction.